The in vitro toxicity of atrazine on kinematics and DNA fragmentation in common carp (Cyprinus carpio) sperm cells - ÖZGÜR, M.E. (Journal of the Hellenic Veterinary Medical Society, 2019)
This study investigated the in vitro effects of different concentrations of Atrazine (0.001, 0.01, 0.1, 0.5 mg/L) added to motile and immotile solutions on kinematics quality of sperm cells of common carp, Cyprinus carpio, which is a fish of economic significance. The kinematics of the sperm cells was analyzed by a computer-assisted sperm analysis system (CASA). As a result of the study, while there was a significant difference (P < 0.05) between the groups in terms of the VSL (μm/s) and VCL (μm/s) values after the Atrazine-added immotile solution’s (IMS) and incubation for 3 hours, there was a significant difference (P < 0.05) in only the VSL values directly activated by the Atrazine-added motile solution (MS). DNA fragmentation was evident but not in higher numbers in the 0.1 mg/L atrazine group. Finally, it was determined the effective concentration (EC50) values of the VSL value of the motile and immotile solution as 0.34 mg/L and 0.03 mg/L, respectively.